Development of Web-Based Promotional Media for UPTD Elementary School 03 Pangkalan, Jorong Banjaranah, Pangkalan Koto Baru Subdistrict, Lima Puluh Kota Regency - Maulana, Yoki Hasra; zahmi, April; Nasir, Janurdi; Saputra, Roni (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
In the field of education, the need for fast and accurate access to information is essential for teachers, students, and parents. To support effective and efficient information delivery at SD Negeri 03 Pangkalan (Elementary School), a web-based information system has been developed to facilitate the management of school data, news, announcements, achievements, and contacts. This study aims to design and implement a web-based information system using the Waterfall approach as the system development model. Data collection techniques used include interviews and observation. The design of the web-based school information system at SD Negeri 03 Pangkalan employs the UML (Unified Modeling Language) development method, consisting of Use Case Diagrams, Activity Diagrams, Sequence Diagrams, and Class Diagrams. The database design uses MySQL, and the system interface was developed using XAMPP as the web server, with PHP and MySQL for the database. The results of this study are a web-based system that can assist the school in managing and distributing information digitally, enhancing transparency, and facilitating user access. The conclusion of this study indicates that the implementation of a web-based information system can improve communication and school promotion effectiveness, as well as ease the management of necessary data.